Aulactinia sinensis, a new species of sea anemone (Cnidaria: Anthozoa: Actiniaria) from Yellow Sea - Li, Yang; Liu, Rui-Yu (Zootaxa, 2012)
Aulactinia sinensis, a new species of sea anemone collected from the intertidal zone of Qingdao, Yellow Sea, is describedand illustrated. This species is elongated, becoming plump distally, has circumscribed sphincter, and with 48 vertical rowsof verrucae in upper column, 48 pairs of mesenteries and 96 short tentacles. It is similar in shape to A. capitata Agassizin Verrill, 1864, but distinguished by its smaller basitrichs in tentacles and larger microbasic p-mastigophores in actinopharynx and mesenterial filaments.